Metabolic Changes Associated With Cardiomyocyte Dedifferentiation Enable Adult Mammalian Cardiac Regeneration. Issue 25 (24th November 2022) - Cheng, Yuan-Yuan; Gregorich, Zachery; Prajnamitra, Ray P.; Lundy, David J.; Ma, Ting-Yun; Huang, Yu-Hsuan; Lee, Yi-Chan; Ruan, Shu-Chian; Lin, Jen-Hao; Lin, Po-Ju; Kuo, Chiung-Wen; Chen, Peilin; et al.
Abstract : Background: Cardiac regeneration after injury is limited by the low proliferative capacity of adult mammalian cardiomyocytes (CMs). However, certain animals readily regenerate lost myocardium through a process involving dedifferentiation, which unlocks their proliferative capacities. Methods: We bred mice with inducible, CM-specific expression of the Yamanaka factors, enabling adult CM reprogramming and dedifferentiation in vivo. Results: Two days after induction, adult CMs presented a dedifferentiated phenotype and increased proliferation in vivo. Microarray analysis revealed that upregulation of ketogenesis was central to this process. Adeno-associated virus-driven HMGCS2 overexpression induced ketogenesis in adult CMs and recapitulated CM dedifferentiation and proliferation observed during partial reprogramming. This same phenomenon was found to occur after myocardial infarction, specifically in the border zone tissue, and HMGCS2 knockout mice showed impaired cardiac function and response to injury. Finally, we showed that exogenous HMGCS2 rescues cardiac function after ischemic injury. Conclusions: Our data demonstrate the importance of HMGCS2-induced ketogenesis as a means to regulate metabolic response to CM injury, thus allowing cell dedifferentiation and proliferation as a regenerative response.